ANALISIS PERMILIHAN KARTU KREDIT DENGAN METODE THE ANALYTICAL HIERARCHY PROCESS (AHP) - , Chitra Tri Jayanti S.; , Adi Djoko Guritno, Dr., M.SIE ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Purchasing power of people are growing, lifestyle is changing, initially from cash payment switch into debit or credit card payment. Credit cards provide convinience, attractive offers, adjusted payment system based on customerâs need and abilities and give credit services to customer credit card limit. This study aims to identify and analyze the criteria that influence customer in selecting credit card, and to propose alternative that suits the respondents criteria in choosing credit card by using The Analytical Hierarchy Process (AHP). AHP is multi-objective, multicriteria theory of measurement. It addresses the issue of how to structure a complex decision problem, identify its criteria, measure the interaction among them and finally synthesize all the information to arrive at priorities which depict preferences. Data of respondents was collected using three different questionnaires: employees, housewifes and students who have and understand the three credit cards which is Bank Mandiri, BCA and Citibank. The result of analysis shows that the main factors that influenced respondent in choosing credit card are